Sinergitas Satuan Polisi Pamong Praja (Satpol PP) Dan Dinas Perhubungan Dalam Pelaksanaan Penertiban Pedagang Kaki Lima (PKL) Di Kota Denpasar (Studi Kasus: Penertiban Di Pasar Wangaya, Jalan RA Kartini, Kelurahan Dauh Puri Kaja, Kecamatan Denpasar Utara) - Deviani, Ni Luh Putu; Sastra Wijaya, Komang Adi; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2021)
Synergy between the Satpol PP of Denpasar City and the Denpasar City Transportation Service, it is hoped that they will be able to curb street vendors in Denpasar City, especially on RA Kartini street, Wangaya market Denpasar area in order to create order and security on the road. This study used a qualitative descriptive method with data collection techniques1 in the form of observation1, interview1 and documentation1. This study looks at how the synergy between the Satpol PP of Denpasar City and the Denpasar City Department of Transportation in the implementation of curbing street vendors in Denpasar City, especially on RA Kartini street, Wangaya market Denpasar area by using the Najiyati synergy indicator which consists of communication and coordination. The results showed that the synergy was running well based on communication and coordination indicators. Need to be improved so that the synergy can run more optimally. Keywords: Synergy, Control, Curbing, Street Vendors.